Role of Mi-2 in chromatin regulation to regulate neural stem cell fate and life-span in Drosophila melanogaster - Venda, Ana Margarida Ramalho (2018)
Tese de mestrado, Ciências Biofarmacêuticas, Universidade de Lisboa, Faculdade de Farmácia, 2017